Fast Volume Generation Molecule Reservoirs on DSMC Stream Boundaries - Sengil, N.; Edis, Firat O.; Abe, Takashi (AIP, 2008)
If stream boundaries exist in flows simulated with molecular methods such as Direct Simulation Monte Carlo (DSMC), molecules inside the flow zone can leave the zone from these boundaries. At the same time some new molecules are introduced into the flow area through the stream boundaries. The number of new molecules and their velocities are calculated from the stream boundary conditions. Mostly two different methods are employed to perform stream boundary calculations. These are surface and volume generation reservoir methods. Each method has some advantages over the other. Two important disadvantages of the volume generation reservoir method are the lower number flux of the molecules compare with the theoretical number flux and lower computational efficiency compare to surface generation reservoir method. In this study it is shown that using a new approach to volume generation reservoir method, these disadvantages can be avoided.